The Energetic Particle Population in Centaurus A. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Chadwick, Paula; Brown, Anthony M.; Boehm, Celine; Graham, Jamie; Lacroix, Thomas; Silk, Joseph
Abstract: We report a significant hardening of the Fermi -LAT gamma-ray spectrum from the core of Cen A at E > 2.4 GeV, suggesting there is a source of high energy particles in the core of Cen A which is in addition to the jet component. We show that the observed gamma-ray spectrum is compatible with either a spike in the dark matter halo profile or a population of millisecond pulsars. This work gives a strong indication of new gamma-ray production mechanisms in active galactic nuclei and could even provide evidence for the clustering of heavy dark matter particles around black holes.